Pengaruh Benzil Amino Purin Terhadap Pertumbuhan Durian (Durio Zibethinus Murr) Sambung pucuk - Aisyah Rahim; Widodo Haryoko (Jurnal Embrio, 2025)
The purpose of this study is to determine the best concentration of benzyl amino purine (BAP) on the growth of durian seedlings (Durio zibethinus Murr.) grafted on the shoots of the durian kunik variety. This research was carried out from October 2024 to January 2025 at the main garden of the Agricultural Extension Center, Agriculture and Food Security Office, 2x11 Kayutanam District, Padang Pariaman Regency, West Sumatra. The design used was a one-factor Complete Random Design (RAL) with 5 levels of treatment. Each treatment was repeated 5 times. The observed variables were the percentage of live joints, the increase in the length of the entres, the increase in the height of the upper stem, the diameter of the rootstock, the increase in the diameter of the upper stem and the number of leaves. The result data was analyzed of variants at the 5% level and further tested at the DNMRT level of 5%. The results of the study on the concentration of BAP Benzyl Amino Purine) at a concentration of 400 ppm had a real effect on the success of grafting the shoots of Durian plants. Keywords: Durian, BAP, seedlings